Successful Conservative Management of a Dislocated IUD - Hasan Ali Inal; Zeynep Ozturk Inal; Ender Alkan (Case Reports in Obstetrics and Gynecology)
Background. Intrauterine contraceptive devices (IUDs) are widely utilized all over the world owing to their low cost and high efficacy. Uterine perforation is a rare complication that may occur at IUD insertion resulting in extrauterine location of the IUD. Traditionally, surgical removal of dislocated IUDs has been recommended. Case. A 68-year-old patient who had an IUD (Lippes loop) inserted 32 years ago and whose routine examination incidentally revealed a dislocated IUD in the abdominal cavity. The patient remained asymptomatic during three years of follow-up and the IUD was left in place. Conclusion. Asymptomatic patients, whose vaginal examinations and ultrasonography or X-ray results reveal a dislocated IUD, may benefit from conservative management.